Development and Characterization of Poly-ε-caprolactone Nanocapsules Containing β-carotene Using the Nanoprecipitation Method and Optimized by Response Surface Methodology - Lino,Renata Calegari (2020)
Abstract Nanoparticles demonstrate an important role in the protection of bioactive compounds from external factors such as temperature, oxygen and light. In this study, poly-ε-caprolactone (PCL) nanoparticles entrapped β-carotene was produced using the nanoprecipitation method. Firstly, was evaluated the lipophilic surfactant effect and carrier agent of the active compound in the nanocapsules formulation. After choosing the most stable formulation, the nanocapsules production was optimized using β-carotene, caprylic/capric triglycerides (CCT) and soybean lecithin. Response surface methodology (RSM) was adopted to evaluate the influence of soy lecithin concentration, volume of CCT and β-carotene concentration in the particle size, zeta potential, polydispersity index (PDI), encapsulation efficiency and recovery. Formulations containing soy lecithin and CCT demonstrated better stability comparing to the other formulations tested. The nanoparticle formulations presented an optimized particle size below 200 nm, PDI lower than 0.1 and encapsulation efficiency above 95%. Based on the results obtained, the optimum conditions to prepare PCL nanocapsules were 0.2160 mg/mL of β-carotene, 232.42 μL of CCT and 2.59 mg/mL of soy lecithin, suggesting an applicability to promote controlled released of β-carotene in food system.